Strategi Pembelajaran Pendidikan Islam Anak Usia Dini (PIAUD) Bagi Guru dan Orang Tua dalam Meningkatkan Kualitas Pemahaman Peserta Didik - Sri Hasnawati (Al-Ishlah: Jurnal Pendidikan Islam, 2022)
The task of PIAUD teachers in managing the learning process will be successful if they are supported by professional management and coordination of education and teaching supported by a strong mastery of concepts and ways of working, basic knowledge relations with work practices and support for imaginative and creative ways of thinking. Therefore, the role of educators in schools and the participation of parents in the family environment at very important in responding to the learning strategies applied, so that integration and synergy are realized in increasing student understanding. One of the strategic offers of PIAUD learning programs in improving the quality of understanding of students in learning by involving the participation of parents through parenting learning programs, namely educational efforts carried out by families or parents by utilizing available resources in the family and the environment in the form of activities. learn independently, integrated and integralistic